Deconstructing the Empire: BRICS and the Rise of a Multipolar World - Chanif Ainun Naim; Fitriatul Hasanah (Andalas Institute of International Studies UNAND, 2024)
This study examines the rise of BRICS (Brazil, Russia, India, China, and South Africa) and its impact on the global political economy through Hardt and Negriâ€™s concept of â€œEmpire.â€ BRICS has challenged Western dominance by leveraging economic globalization to build influential networks, reflecting trends of deterritorialization and decentralization. Key strategies include Chinaâ€™s push for internet sovereignty and Russiaâ€™s market realignment under Western sanctions. The recent expansion of BRICS to include Egypt, Ethiopia, Iran, Saudi Arabia, and the UAE underscores its growing influence in reshaping global governance. However, the study also identifies elements of â€œEmpireâ€ within BRICS, such as the use of economic leverage and biopower to exert control. These findings reveal a complex interplay between power and resistance, where BRICS, while challenging Western hegemony, also replicates some control mechanisms. This research contributes to the theoretical discourse on globalization and provides practical insights into the evolving multipolar world order.